Strategi Komunikasi Humas Polda Daerah Istimewa Yogyakarta Dalam Membangun Kepercayaan Masyarakat Terhadap Kepolisian Dalam Menangani Kejahatan Jalanan - Nurkholis Adi Pamungkas (Jurnal Impresi Indonesia, 2025)
This study aims to determine the communication strategy carried out by the Yogyakarta Special Region Police Public Relations in building public trust in the police, especially in handling street crimes that are rampant in the Yogyakarta area. Street crimes or what are known to the public as "klitih" have become a public concern because they create a sense of insecurity and lower the image of the police. This study uses a qualitative descriptive approach with data collection techniques through in-depth interviews, observation, and documentation. Informants in this study include members of the Yogyakarta Special Region Police Public Relations, community leaders, and the general public. The results of the study show that the Yogyakarta Special Region Police Public Relations implements a communication strategy that refers to the seven elements of strategic communication according to Cutlip, Center, and Broom, namely: credibility, context, content, clarity, continuity and consistency, channel, and capability of the audience. In addition, the communication strategy is implemented through two channels, namely external and internal communication by optimizing social media, mass media, official websites, and cooperation with various elements of society. A humanistic approach, openness of information, and cross-sector collaboration are important keys in forming a positive image of the police. This study concludes that the communication strategy implemented by the DIY Regional Police Public Relations is quite effective in increasing public trust, although improvements are still needed in delivering messages to make them easier for the wider community to understand.